A Novel CD133- and EpCAM-Targeted Liposome With Redox-Responsive Properties Capable of Synergistically Eliminating Liver Cancer Stem Cells - Wang, Zihua; Sun, Mengqi; Li, Wang; Fan, Linyang; Zhou, Ying; Hu, Zhiyuan (Frontiers in Chemistry, 2020)
Cancer stem cells (CSCs) are a small subset of cells that sit atop the hierarchical ladder in many cancer types. Liver CSCs have been associated with high chemoresistance and recurrence rates in hepatocellular carcinoma (HCC). However, as of yet, no satisfactorily effective liver CSC-targeted treatment is available, which drove us to design and investigate the efficacy of a liposome-based delivery system. Here, we introduce a redox-triggered dual-targeted liposome, CEP-LP@S/D, capable of co-delivering doxorubicin (Dox) and salinomycin (Sal) to synergistically treatment liver cancer. This system is based on the association of CD133- and EpCAM-targeted peptides to form Y-shaped CEP ligands that were anchored to the surface of the liposome and allowed the selective targeting of CD133+ EpCAM+ liver CSCs. After arriving to the CSCs, the CEP-LP@S/D liposome undergoes endocytosis to the cytoplasm, where a high concentration of glutathione (GSH) breaks its disulﬁde bonds, thereby degrading the liposome. This then induces a rapid release of Dox and Sal to synergistically inhibit tumor growth. Notably, this effect occurs through Dox-induced apoptosis and concurrent lysosomal iron sequestration by Sal. Interestingly, both in vitro and in vivo studies indicated that our GSH-responsive co-delivery system not only effectively enhanced CSC targeting, but also eliminated the non-CSC faction, thereby exhibiting high antitumor efﬁcacy. We believe that the smart liposome nanocarrier-based co-delivery system is a promising strategy to combat liver cancer, which may also lay the groundwork for more enhanced approaches to target other cancer types as well.